Antibacterial and detoxicating leather coating and preparation method thereof
By using nano ZnO/Ag composite particles in conjunction with chlorhexidine hydrochloride, combined with polyacrylic resin and polyoxyethylene hydrogenated castor oil, a leather coating with excellent antibacterial and antitoxic properties was prepared, which solved the shortcomings of antibacterial properties in the prior art and Weather resistance issues achieve a wider antibacterial spectrum and stable coating performance.
Patent Information
- Application Number
- CN202411697127.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing antibacterial leather coatings have insufficient performance in improving hygiene and safety, especially in terms of long-term use and weather resistance.
Nano ZnO/Ag composite particles are used in conjunction with chlorhexidine hydrochloride, and nano ZnO/Ag composite particles are prepared by stirring, ultrasonication, freeze-drying and calcining, and combined with polyacrylic resin, polyoxyethylene hydrogenated castor oil and other components to form Leather coating with excellent antibacterial and antitoxic properties.
It significantly improves the antibacterial efficiency and physical and chemical stability of the coating, enhances the safety and environmental protection of leather products, while maintaining good flexibility and feel.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of leather coating preparation, and relates to an antibacterial and detoxifying leather coating and a preparation method thereof. Background Art
[0002] Leather finishing agent is a polymer compound that is evenly coated on the surface of leather. It forms one or more layers of film on the surface of leather products through adhesion. Therefore, the quality of coating materials not only affects the appearance and quality of the product, but also largely determines the performance of the product. With the improvement of people's awareness of health and environmental protection, antibacterial materials have been widely used in many fields such as automotive interiors, furniture, and clothing. As an important form of antibacterial leather coating, antibacterial agents are added to inhibit or kill bacteria, viruses and other microorganisms on the leather surface to improve the hygiene and safety of the product.
[0003] Antimicrobial agents can be divided into two categories: organic antimicrobial agents and inorganic antimicrobial agents, depending on the properties of their materials. Organic antimicrobial agents include synthetic antimicrobial agents and natural antimicrobial agents, which have broad-spectrum antimicrobial properties and are widely used; inorganic antimicrobial agents mainly achieve antimicrobial effects through metal ions such as silver, copper, zinc and their compounds, and have the advantages of good heat resistance and high safety. Nanomaterials such as nanosilver and nano ZnO have extremely large specific surface areas and active centers, which can significantly improve antimicrobial properties. In particular, nanosilver particles release silver ions to interact with proteins and DNA in bacterial cells, destroying bacterial structures and achieving excellent antimicrobial effects. Summary of the invention
[0004] The purpose of the present invention is to provide an antibacterial and detoxifying leather coating and a preparation method thereof, which has the characteristics of good antibacterial and detoxifying performance.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antibacterial and detoxifying leather coating, wherein the leather coating has the following formula: by mass percentage, 20-30% polyacrylic acid resin, 10-15% nano ZnO / Ag composite particles, 15-17% polyoxyethylene hydrogenated castor oil, 10-15% chlorhexidine hydrochloride, 20-30% deionized water, 1-2% dispersant, and 2-3% plasticizer; The preparation method of nano ZnO / Ag composite particles is as follows: S1.1: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a mass fraction of 30%, add nanosilver particles to the zinc nitrate solution, stir at a speed of 200 r / min for 0.5 h, and then ultrasonicate for 0.5 h to obtain a solid-liquid mixture A; S1.2: The solid-liquid mixture A was placed in liquid nitrogen and frozen for 15 min. After the freezing was completed, it was dried at -70 °C under vacuum for 3 h to obtain a mixture B; S1.3: Add 0.5 wt% of polyethylene glycol 2000 to mixture B, grind in a ball mill at a speed of 400 r / min for 0.5 h, heat the ground mixture from room temperature to 400°C and calcine for 3 h, crush and grind the calcined solid to obtain nano ZnO / Ag composite particles.
[0006] Furthermore, the dispersant is one of Tween-60 and Tween-80.
[0007] Furthermore, the plasticizer is one of dioctyl phthalate and diisononyl phthalate.
[0008] Furthermore, the mass ratio of zinc nitrate hexahydrate to the nano-silver particles in S1.1 is 1:1.
[0009] Furthermore, the heating rate in S1.3 is 5°C / min.
[0010] Furthermore, the particle size of the nano ZnO / Ag composite particles obtained by grinding in S1.3 is 200 mesh.
[0011] A method for preparing an antibacterial and detoxifying leather coating. The specific process of the method for preparing the leather coating is as follows: S7.1: heat the polyacrylic acid resin to 165-175°C, stir it in a stirrer at a speed of 300 r / min for 1-2 h, add deionized water at a volume ratio of 1:1 after stirring evenly, continue stirring at a speed of 200 r / min for 2 h after adding deionized water, and slowly cool it to 40-50°C while stirring to obtain a polyacrylic acid resin solution; S7.2: Add polyoxyethylene hydrogenated castor oil to the polyacrylic acid resin solution according to the formula ratio, stir in a stirrer at a rate of 200 r / min for 1 to 2 h to obtain a mixed solution C; S7.3: Chlorhexidine hydrochloride and nano ZnO / Ag composite particles are mixed according to the formula ratio, dispersed in the mixed solution C after mixing evenly, and then a dispersant and a plasticizer are added. Ultrasound is performed for 1 to 2 hours, and ozone is introduced during the ultrasound. After the ultrasound is completed, the ozone introduction is stopped, and nitrogen is introduced for 1 hour for purging. After the purging is completed, the leather coating is allowed to stand for 6 to 8 hours to obtain the leather coating.
[0012] Furthermore, the slow cooling rate in S7.1 is 2°C / min.
[0013] Furthermore, the ozone introduction rate in S7.3 is 20 m / s.
[0014] Furthermore, the nitrogen inlet flow rate in S7.3 is 10 m / s.
[0015] Nano ZnO and nano Ag both have good antibacterial properties. As a wide bandgap semiconductor material, ZnO has excellent antibacterial activity and can destroy the cell wall and cell membrane of bacteria, thereby achieving a bactericidal effect. Ag nanoparticles release silver ions to bind to proteins in bacteria, causing them to denature and inactivate, and also have excellent antibacterial ability. Therefore, combining these two materials together can further enhance their antibacterial effect and form a more powerful antibacterial system. Secondly, the nano ZnO / Ag composite particles also have good detoxification performance. Both ZnO and Ag can react with some toxic substances and convert them into harmless or low-toxic substances, thereby purifying the environment. The application of this composite particle in leather coating can effectively remove harmful substances in leather and improve the safety and environmental protection of leather products; in addition, the nano ZnO / Ag composite particles also have excellent physical and chemical stability. Due to the size effect and surface effect of nanoparticles, this composite particle can be better dispersed and stably exist in the leather coating, and it is not easy to agglomerate and precipitate. At the same time, its good weather resistance and chemical corrosion resistance can also ensure that the leather coating maintains stable performance during long-term use.
[0016] In the process of preparing nano ZnO / Ag composite particles, the present invention can effectively disperse nano silver particles uniformly in zinc nitrate solution by stirring and ultrasonic treatment. This helps to ensure that nano silver and ZnO can be uniformly compounded in the subsequent preparation process to form composite particles with stable performance; the freeze drying process can quickly solidify the solid-liquid mixture at low temperature to avoid agglomeration of nano particles, while maintaining the original structure of the mixture. This helps to form composite particles with good dispersibility and structural stability in the subsequent roasting process; the final roasting process can form stable chemical bonds between nano particles at high temperature, thereby obtaining nano ZnO / Ag composite particles with excellent performance. Roasting can also remove organic impurities in the mixture and improve the purity and stability of the composite particles.
[0017] Polyacrylic acid resin has excellent film-forming properties. As the main film-forming substance of the coating, it provides good adhesion and wear resistance. Polyacrylic acid resin can form a uniform and dense coating on the leather surface to protect the leather from erosion by the external environment. Polyoxyethylene hydrogenated castor oil is used as a softener to improve the flexibility and feel of the coating. It can reduce the hardness of the coating, increase its flexibility and ductility, make the coating more fit to the leather surface, and not easily separated and fallen off. Chlorhexidine hydrochloride is a broad-spectrum antibacterial agent. It can be adsorbed on the surface of bacteria through electrostatic action, destroying the cell wall and cell membrane of bacteria, resulting in leakage of bacterial contents and bacterial death. In addition, chlorhexidine hydrochloride can also interfere with the enzyme activity and metabolic process in bacteria, further inhibiting the growth and reproduction of bacteria. The addition of chlorhexidine hydrochloride can further enhance the antibacterial properties of the coating.
[0018] There is a synergistic effect between nano ZnO / Ag composite particles and chlorhexidine hydrochloride. Both are antibacterial agents, but their mechanisms of action are different. Nano ZnO / Ag composite particles kill bacteria mainly by destroying the cell structure of bacteria, while chlorhexidine hydrochloride inhibits bacteria by destroying the cell wall and cell membrane of bacteria.
[0019] When nano ZnO / Ag composite particles and chlorhexidine hydrochloride are present at the same time, they can enhance each other's antibacterial effect. On the one hand, the presence of nanoparticles can increase the contact area between bacteria and antibacterial agents and improve the utilization rate of antibacterial agents; on the other hand, chlorhexidine hydrochloride can destroy the cell wall and cell membrane of bacteria, making bacteria more vulnerable to attack by nanoparticles. This interaction can form a wider antibacterial spectrum and significantly improve the antibacterial efficiency of the coating.
[0020] Polyacrylic acid resin provides adhesion and abrasion resistance, while plasticizer and polyoxyethylene hydrogenated castor oil increase the flexibility and ductility of the coating. Their combined use ensures that the coating maintains good flexibility and feel while maintaining antibacterial and detoxification properties.
[0021] During the preparation process, the introduction of ozone can sterilize the coating solution to ensure the hygiene and safety of the coating. The introduction of nitrogen for 1 hour can remove residual gas and impurities in the coating solution and improve the purity and quality of the coating. After purging, it is allowed to stand for 6 to 8 hours to fully stabilize the coating solution and eliminate possible bubbles and unevenness, providing a good foundation for subsequent coating and curing.
[0022] The polyacrylic acid resin in the present invention was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., CAS No. 24938-16-7; the polyoxyethylene hydrogenated castor oil in the present invention was purchased from Chengdu Huaxia Chemical Reagent Co., Ltd., CAS No. 61788-85-0; and the chlorhexidine hydrochloride in the present invention was purchased from Xi'an Fanghao Chemical Co., Ltd., CAS No. 3697-42-5.
[0023] Beneficial effects of the present invention: (1) In the process of preparing nano ZnO / Ag composite particles, the present invention uses a freeze-drying process to quickly solidify the solid-liquid mixture at low temperature to avoid agglomeration of the nano particles while maintaining the original structure of the mixture. Then, a calcination process is performed at high temperature to form stable chemical bonds between the nano particles, thereby obtaining nano ZnO / Ag composite particles with excellent performance. In addition, calcination can also remove organic impurities in the mixture and improve the purity and stability of the composite particles.
[0024] (2) The present invention uses nano ZnO / Ag composite particles and chlorhexidine hydrochloride in a synergistic manner, which can enhance the antibacterial effect of each other. On the one hand, the presence of nano particles can increase the contact area between bacteria and antibacterial agents, thereby improving the utilization rate of antibacterial agents. On the other hand, chlorhexidine hydrochloride can destroy the cell walls and cell membranes of bacteria, making the bacteria more vulnerable to attack by nano particles. This interaction can form a broader antibacterial spectrum and significantly improve the antibacterial efficiency of the coating. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] Formula ratio 1: polyacrylic acid resin 25%, nano ZnO / Ag composite particles 15%, polyoxyethylene hydrogenated castor oil 15%, chlorhexidine hydrochloride 15%, deionized water 25%, Tween-60 2%, dioctyl phthalate 3%; Formula ratio 2: polyacrylic acid resin 30%, nano ZnO / Ag composite particles 10%, polyoxyethylene hydrogenated castor oil 16%, chlorhexidine hydrochloride 10%, deionized water 30%, Tween-60 1%, diisononyl phthalate 3%; Formula ratio 3: polyacrylic acid resin 25%, nano ZnO / Ag composite particles 15%, polyoxyethylene hydrogenated castor oil 17%, chlorhexidine hydrochloride 15%, deionized water 25%, Tween-80 1%, dioctyl phthalate 2%; The preparation method of nano ZnO / Ag composite particles is as follows: S1.1: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a mass fraction of 30%, add nanosilver particles to the zinc nitrate solution, the mass ratio of zinc nitrate hexahydrate to nanosilver particles is 1:1, stir at a speed of 200 r / min for 0.5 h after adding, and then ultrasonicate for 0.5 h after stirring to obtain a solid-liquid mixture A; S1.2: The solid-liquid mixture A was placed in liquid nitrogen and frozen for 15 min. After the freezing was completed, it was dried at -70 °C under vacuum for 3 h to obtain a mixture B; S1.3: Add 0.5wt% of polyethylene glycol 2000 to mixture B, grind in a ball mill at a speed of 400r / min for 0.5h, heat the ground mixture from room temperature to 400℃ and calcine for 3h at a heating rate of 5℃ / min, crush and grind the calcined solid to obtain nano ZnO / Ag composite particles with a particle size of 200 mesh.
[0027] Example 1 The specific process of the preparation method of leather coating is as follows: S7.1: Heat the polyacrylic acid resin to 170°C, stir it in a stirrer at a speed of 300 r / min for 1.5 hours, add deionized water at a volume ratio of 1:1 after stirring evenly, continue to stir at a speed of 200 r / min for 2 hours after adding deionized water, and slowly cool it to 40°C while stirring at a rate of 2°C / min to obtain a polyacrylic acid resin solution; S7.2: Add polyoxyethylene hydrogenated castor oil to the polyacrylic acid resin solution according to the formula ratio 1, stir the mixture in a stirrer at a rate of 200 r / min for 1.5 h to obtain a mixed solution C; S7.3: Chlorhexidine hydrochloride and nano ZnO / Ag composite particles are mixed according to the formula ratio 1, and dispersed in the mixed solution C after mixing evenly. Dispersant and plasticizer are then added, and ultrasonic treatment is performed for 2 hours. Ozone is introduced while ultrasonic treatment at a flow rate of 20 m / s. After the ultrasonic treatment is completed, ozone introduction is stopped, and nitrogen is introduced for 1 hour at a flow rate of 10 m / s. After the purging is completed, the leather coating is allowed to stand for 8 hours to obtain the leather coating.
[0028] Example 2 S7.1: Heat the polyacrylic acid resin to 165°C, stir it in a stirrer at a speed of 300 r / min for 2 hours, add deionized water at a volume ratio of 1:1 after stirring evenly, continue to stir at a speed of 200 r / min for 2 hours after adding deionized water, and slowly cool it to 50°C while stirring at a rate of 2°C / min to obtain a polyacrylic acid resin solution; S7.2: Add polyoxyethylene hydrogenated castor oil to the polyacrylic acid resin solution according to the formula ratio 2, stir the mixture in a stirrer at a rate of 200 r / min for 2 h to obtain a mixed solution C; S7.3: Chlorhexidine hydrochloride and nano ZnO / Ag composite particles are mixed according to the formula ratio 2, and dispersed in the mixed solution C after mixing evenly. Dispersant and plasticizer are then added, and ultrasonic treatment is performed for 1 hour. Ozone is introduced at the same time as ultrasonic treatment, and the ozone introduction rate is 20 m / s. After the ultrasonic treatment is completed, ozone introduction is stopped, and nitrogen is introduced for 1 hour for purging, and the nitrogen introduction rate is 10 m / s. After the purging is completed, the leather coating is allowed to stand for 6 hours to obtain the leather coating.
[0029] Example 3 S7.1: Heat the polyacrylic acid resin to 175°C, stir it in a stirrer at a speed of 300 r / min for 1 hour, add deionized water at a volume ratio of 1:1 after stirring evenly, continue to stir at a speed of 200 r / min for 2 hours after adding deionized water, and slowly cool it to 40-50°C while stirring at a rate of 2°C / min to obtain a polyacrylic acid resin solution; S7.2: Add polyoxyethylene hydrogenated castor oil to the polyacrylic acid resin solution according to the formula ratio 1, stir the mixture in a stirrer at a rate of 200 r / min for 1 h to obtain a mixed solution C; S7.3: Chlorhexidine hydrochloride and nano ZnO / Ag composite particles are mixed according to the formula ratio 1, and dispersed in the mixed solution C after mixing evenly. Dispersant and plasticizer are then added, and ultrasonic treatment is performed for 1 hour. Ozone is introduced at the same time of ultrasonic treatment at a flow rate of 20 m / s. After the ultrasonic treatment is completed, ozone introduction is stopped, and nitrogen is introduced for 1 hour at a flow rate of 10 m / s. After the purging is completed, the leather coating is allowed to stand for 8 hours to obtain the leather coating.
[0030] Comparative Example 1 In this comparative example, no freeze-drying treatment was performed during the preparation of the nano ZnO / Ag composite particles, and the remaining steps were consistent with those of Example 1.
[0031] Comparative Example 2 In this comparative example, no calcination treatment is performed during the preparation of the nano ZnO / Ag composite particles, and the remaining steps are consistent with those of Example 1.
[0032] Comparative Example 3 In this comparative example, chlorhexidine hydrochloride was not added during the preparation process, and the remaining steps were consistent with those in Example 1.
[0033] Comparative Example 4 In this comparative example, polyoxyethylene hydrogenated castor oil was not added during the preparation process, and the remaining steps were consistent with those in Example 1.
[0034] The performance of the embodiments and comparative examples was tested, and the antibacterial rate (%) was tested according to GB / T 20944.3-2008. The experimental results are summarized in the following table:
[0035] The embodiments and comparative examples were tested, and the experiments showed that the freeze-drying and calcining treatments in the preparation process of the nano ZnO / Ag composite particles effectively improved the antibacterial properties of the coating, the addition of chlorhexidine hydrochloride further improved the antibacterial properties of the coating, and the addition of polyoxyethylene hydrogenated castor oil made the coating have better adhesion properties, thereby effectively improving the antibacterial properties of the coating.
[0036] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. An antibacterial and detoxifying leather coating, characterized in that: The leather coating has the following formula: by mass percentage, 25-30% polyacrylic acid resin, 10-15% nano ZnO / Ag composite particles, 15-17% polyoxyethylene hydrogenated castor oil, 10-15% chlorhexidine hydrochloride, 25-30% deionized water, 1-2% dispersant, and 2-3% plasticizer; The preparation method of nano ZnO / Ag composite particles is as follows: S1.1: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a mass fraction of 30%, add nanosilver particles to the zinc nitrate solution, stir at a speed of 200 r / min for 0.5 h, and then ultrasonicate for 0.5 h to obtain a solid-liquid mixture A; S1.2: The solid-liquid mixture A was placed in liquid nitrogen and frozen for 15 min. After the freezing was completed, it was dried at -70 °C under vacuum for 3 h to obtain a mixture B; S1.3: Add 0.5 wt% of polyethylene glycol 2000 to mixture B, grind in a ball mill at a speed of 400 r / min for 0.5 h, heat the ground mixture from room temperature to 400°C and calcine for 3 h, crush and grind the calcined solid to obtain nano ZnO / Ag composite particles.
2. The antibacterial and detoxifying leather coating according to claim 1, characterized in that: The dispersant is one of Tween-60 and Tween-80.
3. The antibacterial and detoxifying leather coating according to claim 1, characterized in that: The plasticizer is one of dioctyl phthalate and diisononyl phthalate.
4. The antibacterial and detoxifying leather coating according to claim 1, characterized in that: The mass ratio of zinc nitrate hexahydrate to nano-silver particles in S1.1 is 1:
1.
5. The antibacterial and detoxifying leather coating according to claim 1, characterized in that: The heating rate in S1.3 is 5°C / min.
6. The antibacterial and detoxifying leather coating according to claim 1, characterized in that: The particle size of the nano ZnO / Ag composite particles obtained by grinding in S1.3 is 200 mesh.
7. A method for preparing an antibacterial and detoxifying leather coating, based on the antibacterial and detoxifying leather coating according to any one of claims 1 to 6, characterized in that: The specific process of the preparation method of leather coating is as follows: S7.1: heat the polyacrylic acid resin to 165-175°C, stir it in a stirrer at a speed of 300 r / min for 1-2 h, add deionized water at a volume ratio of 1:1 after stirring evenly, continue stirring at a speed of 200 r / min for 2 h after adding deionized water, and slowly cool it to 40-50°C while stirring to obtain a polyacrylic acid resin solution; S7.2: Add polyoxyethylene hydrogenated castor oil to the polyacrylic acid resin solution according to the formula ratio, stir in a stirrer at a rate of 200 r / min for 1 to 2 h to obtain a mixed solution C; S7.3: Chlorhexidine hydrochloride and nano ZnO / Ag composite particles are mixed according to the formula ratio, dispersed in the mixed solution C after mixing evenly, and then a dispersant and a plasticizer are added. Ultrasound is performed for 1 to 2 hours, and ozone is introduced during the ultrasound. After the ultrasound is completed, the ozone introduction is stopped, and nitrogen is introduced for 1 hour for purging. After the purging is completed, the leather coating is allowed to stand for 6 to 8 hours to obtain the leather coating.
8. The method for preparing an antibacterial and detoxifying leather coating according to claim 7, characterized in that: The slow cooling rate in S7.1 is 2°C / min.
9. The method for preparing an antibacterial and detoxifying leather coating according to claim 7, characterized in that: The ozone inlet flow rate in S7.3 is 20 m / s.
10. The method for preparing an antibacterial and detoxifying leather coating according to claim 7, characterized in that: The nitrogen inlet flow rate in S7.3 is 10 m / s.
Citation Information
Patent Citations
Preparation method of polyacrylate leather finishing agent
CN103073967A
Water-based paint and antibacterial leather prepared from water-based paint
CN115478440A
Process For Making Nano-Sized and Micro-Sized Precipitate Particles
US20100028236A1
